Income tax progressivity, growth, income inequality and welfare - Cruz A. Echevarría (SERIEs - Journal of the Spanish Economic Association, 2015)
This paper analyzes the effects of personal income tax progressivity on long-run economic growth, income inequality and social welfare. The quantitative implications of income tax progressivity increments are illustrated for the US economy under three main headings: individual effects (reduced labor supply and savings, and increased dispersion of tax rates); aggregate effects (lower GDP growth and lower income inequality); and welfare effects (lower dispersion of consumption across individuals and higher leisure levels, but also lower growth of future consumption). The social discount factor proves to be crucial for this third effect: a higher valuation of future generations' well-being requires a lower level of progressivity. Additionally, if tax revenues are used to provide a public good rather than just being discarded, a higher private valuation of such public goods will also call for a lower level of progressivity.
Keywords: H20; O41; 330; Growth; Income tax progressivity; Income inequality; Welfare